UNPLENARY - AN INVOCATION (BALEAP Journal of Research and Practice, 2025)
In my plenary talk at the 2023 BALEAP Conference, I invoked a number of ghosts who continue to cast long shadows over contemporary critical theory. The first of these was Walter Benjamin, the German-Jewish essayist and cultural critic, famous for the unfinished Arcades project, which was an attempt to uncover the “messianic” elements which lay buried among the cultural objects and artefacts of the nineteenth century. The second was Jacques Derrida, the French Algerian-born philosopher and founder of “Deconstruction”, our conference theme. Like Benjamin, Derrida calls for radical change, for social justice – for what he calls a “messianic without messianism” (1994, p. 74), meaning a complete openness to the future, to the radically different and unanticipated “other” (1994, p. 112). This is accomplished through a process of endless deconstruction – an endless critique of society, culture, language, politics.